Odpowiedzi

2013-07-22T10:51:19+02:00

Zapis tej funkcji w postaci iloczynowej:

 

\\f(x)=a(x+4)(x-3) \\f(-2)=20 \\f(-2)=a(-2+4)(-2-3)=20 \\-10a=20 /:(-10) \\a=-2 \\f(x)=-2(x^2-3x+4x-12) \\f(x)=-2x^2-2x+24 \\Odp. \ a=-2, \ b=-2, \ c=24

 

2013-07-22T11:10:07+02:00

f(x) = ax² + bx + c

x₁ = -4,   x₂ = 3,   P=(-2; 20)

 

f(x) = a(x - x₁)(x - x₂)  - postać iloczynowa trójmianu kwadratowego

20 = a(-2 + 4)(-2 - 3) 

a*2*(-5) = 20

-10a = 20  /:(-10)

a = -2

 

f(-2) = -2(x + 4)(x - 3)

f(-2) = -2(x² - 3x + 4x - 12)

f(-2) = -2(x² + x -12)

f(-2) = -2x² - 2x + 24

 

a = -2

b = -2

c = 24